MULHERES, VIOLÊNCIA CONJUGAL E O SISTEMA ÚNICO DE SAÚDE (SUS): contribuições do serviço de psicologia - Furquim, Giovana Tomé (2020)
Violence is a historical phenomenon of socialization and demonstration of power in which women are often the victims. Supported by feminist movements, women have been claiming their rights within society and, jointly, denouncing the practice of violence that occurred in the domestic sphere, since in many occasions the authors are their own intimate partners. The World Health Organization has intensified the importance of preventing violence against women, as this is a phenomenon that has numerous consequences for the lives and health of these women, especially when it comes to psychological violence which is difficult to identify. In this sense, the present dissertation aims to identify the contributions of Psychology professionals in the Sistema Único de Saúde (SUS) to confront violence against women in the marital relationship. The research used the qualitative method, through semi-structured interview conducted with six women, over 18 years old, who constitute or constituted marital relationships for a minimum period of five years and who sought SUS for care with the psychology professional. The study took place in a city in the countryside of the state of São Paulo. The data collection analyzes were carried out based on the phenomenological method with reference to the Rogerian theoretical perspectives. The results showed: a) the presence of experiences of psychological, physical and/or sexual violence in the marital relationship and in the family context, even before the beginning of the marriage; b) women sought health care to attend to complaints of physical and psychological symptoms and these were not associated, at first, with the phenomenon of violence; c) women found it difficult to seek professional help for the phenomenon of violence; d) it was found that the care provided by the psychology sector was a milestone in the identification of this experience, as well as the possibility of reframing in the face of the phenomenon of violence suffered. In view of the results achieved, it was found that for the services of psychology professionals working in the network to confront violence against women and to carry out the promotion and prevention related to health care, they must be prepared to assist these women identifying situations of violence, since they directly interferes in a dignified and healthy life.